A Study on HR Practices on employee work Engagement in Hospitality Industry: Examining the Impact of HR Policies on Job Engagement in the Hospitality Industry (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A competitive edge is essential for organizations in today's difficult business climate. Thehuman dimension may provide organizations a lasting advantage over their competitors in today's VUCAclimate, organizations have learned. Consequently, it has become imperative for organizations toguarantee that their staff is fully engaged in order to achieve their goals. One of India's most importantindustries is the hospitality sector. As a high-quality service sector that relies heavily on its workforce, thehotel industry's success is directly tied to the quality of its customer service. As a result, this studyexamines how hotel workers evaluate their employer's HR policies and how this affects their jobengagement. As part of the investigation, it attempts to determine if the link is mediated by theperception of organizational support.